2011
DOI: 10.1097/01.xej.0000406600.34603.8d
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of Her2/neu, progesterone receptor, and MIB-1 expression in meningioma

Abstract: Background The clinical progress of meningiomas is difficult to predict, and risk stratification on the basis of histomorphology alone remains problematic. Investigators are currently researching numerous predictive and prognostic factors, aiming to facilitate the identification of patients with meningioma who should be followed more closely for evidence of recurrent tumor or may be treated more aggressively at the time of diagnosis.Aim In the current study, we aimed to investigate the relation between Her-2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Furthermore, 50% of ERBB2-positive cases experienced recurrence. Khamis et al ( 29 ) reported that 34.2% of 38 meningioma cases were ERBB2-positive, with 29% grade I and 57.1% grades II and III. There was no statistically significant association between ERBB2 expression and tumor grade.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 50% of ERBB2-positive cases experienced recurrence. Khamis et al ( 29 ) reported that 34.2% of 38 meningioma cases were ERBB2-positive, with 29% grade I and 57.1% grades II and III. There was no statistically significant association between ERBB2 expression and tumor grade.…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 ] studied expression of Erb B1, Erb B2, Erb B3, and Erb B4 receptors and ligand genes by real-time polymerase chain reaction in various grades of meningiomas and found strong erbB1-erbB2 overexpression and erbB3-erbB4 underexpression in meningioma and suggested that these findings might be useful for gene therapy. In another study published in 2011[ 21 ] revealed highest HER2 immunopositivity in meningothelial subtype of meningioma. Atypical/anaplastic meningioma types showed highest rate HER2 immunopositivity than benign meningiomas.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown higher HER2 expressions in grade I meningiomas (116,117), while other studies have shown no significant differences between grades (7,42,53,113,115,118). In some studies, the relation between HER2 expression and an increase in Ki67 and recurrence was evidenced, indicating that they may be predictors of aggression (51,119).…”
Section: Her2mentioning
confidence: 98%